Outsourcing intelligence: The relationship between the state and Private intelligence in post apartheid South Africa - Butt, Stephen (Department of Political Studies, 2014)
The state claims the monopoly of the legitimate use of force. This is not to suggest however that the state cannot and does not outsource the practical exercise of force. On the contrary, the outsourcing of a wide range of military and security roles and functions is, to a greater or lesser extent, a feature of most states. Important, yet least well understood is the outsourcing of intelligence. Explanations of the outsourcing of this sensitive function usually cite the incapacity of the state and the efficiency of the private sector. But is such outsourcing efficient? The evidence suggests not. Rather the outsourcing of intelligence has been characterized by inefficiency, corruption and criminality. This has certainly proved the case in post-apartheid South Africa where the outsourcing of intelligence by the state has been popular. This dissertation examines the relationship between the state and private intelligence in post-apartheid South Africa. It is divided into three chapters. The first chapter is concerned with establishing key concepts; namely the state, intelligence, and public and private intelligence; and with developing an interpretative framework of the relationship between the state and private intelligence. The second chapter provides an overview of intelligence in South Africa between 1949 and 2008. The third chapter considers the relationship between the state and private intelligence in post-apartheid South Africa. This dissertation concludes that the relationship between the state and private intelligence in post-apartheid South Africa can be best described as contradictory. While on the one hand the state has been hostile towards private intelligence, the outsourcing of intelligence has been favoured by the post-apartheid state. For the most part, such outsourcing has proved inefficient, corrupt and criminal; and has undermined what are already weak mechanisms of oversight and accountability.